1984
DOI: 10.1007/bf00502450
|View full text |Cite
|
Sign up to set email alerts
|

Retardation of cerebral dopamine turnover after morphine withdrawal and its enhanced acceleration by acute morphine administration in rats

Abstract: To clarify the effects of withdrawal from chronic morphine treatment on cerebral dopamine (DA) turnover, we have measured the alpha-methyl-p-tyrosine (alpha MT)-induced depletion of DA in five brain areas of male Wistar rats given morphine twice daily for 40 or 60 days. After the last morphine dose (50 or 70 mg/kg) the rats were withdrawn for 1, 2 or 4 days. In order to study the development of tolerance some of the rats were challenged with 10 mg/kg of morphine. Withdrawal of morphine retarded the alpha MT-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 36 publications
3
15
0
Order By: Relevance
“…Indeed, in several experiments it was found that chronic morphine treatment induces tolerance to the DA turnover enhancing effect of morphine (Fukui and Takagi, 1972;Smith et aL, 1972;De Simoni et aL, 1982). In contrast, we found that the DA depletion accelerating effect of morphine was even enhanced in rats withdrawn from 60-day morphine treatment (Attila and Ahtee, 1984), and a challenge dose of morphine clearly increased the cerebral 5-HIAA concentration in rats withdrawn from 8-week morphine treatment .…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Indeed, in several experiments it was found that chronic morphine treatment induces tolerance to the DA turnover enhancing effect of morphine (Fukui and Takagi, 1972;Smith et aL, 1972;De Simoni et aL, 1982). In contrast, we found that the DA depletion accelerating effect of morphine was even enhanced in rats withdrawn from 60-day morphine treatment (Attila and Ahtee, 1984), and a challenge dose of morphine clearly increased the cerebral 5-HIAA concentration in rats withdrawn from 8-week morphine treatment .…”
Section: Introductionmentioning
confidence: 54%
“…We earlier suggested Ahtee and Attila, 1980;Ahtee, 1983 and1984) that likely causes for reduced cerebral turnover of 5-HT and DA in rats on withdrawal from morphine are tolerant opiate receptors (Tseng et al, 1977) and reduced concentrations of endogenous opioid ligands (Przewtocki et al, 1979;Bergstr6m and Terenius, 1979). Opiate receptors could become tolerant before the endogenous opioid concentrations decrease but after the endogenous opioid concentrations decrease the receptors might regain their sensitivity at least partially.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The stereotypies induced by morphine and other m-opioids in rats treated repeatedly with opioids have been linked to the activation of the striatal dopaminergic system (Morelli et al, 1989). Indeed, we have shown that the e ect of morphine on striatal DA transmission is augmented during withdrawal from chronic morphine treatment (Ahtee et al, 1989;Attila & Ahtee, 1984;Honkanen et al, 1994). Therefore, we investigated whether tolerance develops to the inhibitory component of morphine on striatal DA release, which in turn might contribute to the sensitization of DA release in the withdrawal from repeated opioid treatment.…”
Section: Introductionmentioning
confidence: 85%
“…This sensitization is more apparent in the mesolimbic dopaminergic system (for a review see Kalivas & Stewart, 1991), but the nigrostriatal system also sensitizes during repeated morphine treatment. Thus, during withdrawal from repeated morphine administration, acute challenge with morphine increases the release of DA considerably more than in naõÈ ve animals (Ahtee, 1974;Attila & Ahtee, 1984;Honkanen et al, 1994). Also behavioural e ects of opioids linked to the activation of the nigrostriatal dopaminergic system undergo sensitization during repeated morphine administration (Ahtee, 1974;Babbini & Davis, 1972).…”
Section: Discussionmentioning
confidence: 99%